The Effect of Parental Attachment on Suicidal Ideation in Adolescent Students - Xiao, Mulin (International Journal of Social Sciences and Public Administration, 2025)
With the rapid development of modern society, adolescents are facing increasing psychological pressure, and suicidal tendency has become a serious social problem. This study aims to explore the relationship between parental attachment and suicidal tendency among adolescent students, with a view to providing a scientific basis for prevention and intervention. Through literature analysis method and qualitative research method, the study found that a good parental attachment relationship can effectively help students improve their psychological condition and reduce their risk of suffering from suicide. This paper further explores the effects of family type, parental attachment, discipline style, and family income on children’s suicidal tendencies, and suggests directions for future research. The findings suggest that family diversity and integrity play a crucial role in reducing the risk of suicide among adolescents, and that parental love and support have a profound effect on children’s spiritual growth.